2021
DOI: 10.1007/s11207-021-01796-3
|View full text |Cite
|
Sign up to set email alerts
|

Solar Irradiance Variability Due to Solar Flares Observed in Lyman-Alpha Emission

Abstract: As the Lyman-alpha (Ly$\upalpha $ α ) line of neutral hydrogen is the brightest emission line in the solar spectrum, detecting increases in irradiance due to solar flares at this wavelength can be challenging due to the very high background. Previous studies that have focused on the largest flares have shown that even these extreme cases generate enhancements in Ly$\upalpha $ α of only a few percent above the background. In this study, a supe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…A significant contribution can be noticed from Lyα when the chromosphere is heated above 10 kK, which is possible in strong flares. A recent study of the Lyα contrasts by Milligan (2021) found that C-class flares, with some notable exceptions, produced a far smaller contrast compared to Mor X-class flares. Note, however, that those observations lacked spatial resolution and therefore don't represent the response of a single footpoint but of the global flare.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…A significant contribution can be noticed from Lyα when the chromosphere is heated above 10 kK, which is possible in strong flares. A recent study of the Lyα contrasts by Milligan (2021) found that C-class flares, with some notable exceptions, produced a far smaller contrast compared to Mor X-class flares. Note, however, that those observations lacked spatial resolution and therefore don't represent the response of a single footpoint but of the global flare.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Woods et al (2004) reported that the Lyα line wing is enhanced by about two times while the line core is enhanced by 20% in an X17 flare. Using the Lyα fluxes of more than 400 X-and M-class flares measured by the Geostationary Operational Environmental Satellite (GOES), Milligan et al (2020) found that the Lyα emission has an enhancement of 10% or less in most of the flares, with an average of 1%-4%, while the enhancement is only about 0.1%-0.3% on average for thousands of C-and B-class flares (Milligan 2021). The physical origin of flaring Lyα has also been studied by comparing Lyα with the hard X-ray (HXR) and soft X-ray (SXR) emissions that are associated with nonthermal electrons and thermal plasmas, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The peak enhancement in Lyα emission among the flare sample was found to range from 1.5% to 6.4%. Comparatively, Milligan (2021) reported an average enhancement in Lyα emission of 1.5% for M-class flares, placing two of the three flares in this study above that average. Interestingly, FISM2 estimated Lyα enhancements of <2.5% for each flare.…”
Section: Discussionmentioning
confidence: 42%
“…In a statistical study of 477 M-and X-class flares observed in the E-channel of the Extreme Ultraviolet Sensor on board the Geostationary Operational Environmental Satellite (GOES/ EUVS-E; Viereck et al 2007;Evans et al 2010), Milligan et al (2020) found that typical increases in Lyα were <10%, with a maximum of approximately 30%. A follow-up study of several thousand flares using a superposed epoch analysis revealed average increases of 0.18%-0.35% for B-and C-class flares, and of 1%-4% for M-and X-class ones (Milligan 2021).…”
Section: Introductionmentioning
confidence: 99%